2016
DOI: 10.18203/2320-1770.ijrcog20164636
|View full text |Cite
|
Sign up to set email alerts
|

A pre-experimental study to evaluate the effectiveness of back massage among pregnant women in first stage of labour pains admitted in labour room of a selected hospital, Ludhiana, Punjab, India

Abstract: Background: Labour is a health state that most women aspire to, at some point in their lives. The first thought that comes to the mind of an expecting woman regarding her delivery is the pain of labour. The major role and responsibility of the nurse is in identifying the problems of the woman in labour, providing appropriate information regarding the alternative modalities of pain relief during labour. A pre-experimental study was conducted to evaluate the effectiveness of back massage on pain among pregnant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 5 publications
3
4
0
3
Order By: Relevance
“…They found that the satisfaction scores in the four phases of labor were significantly higher in the group that was administered a massage compared with the control group (Mortazavi et al, ). Similar results were shown in the study by Sethi and Barnabas (). In their study, it is stated that back massage had a significant impact on pain and that back massage had a significant role in the reduction of pain and the improvement of the emotional experience of labor (Sethi & Barnabas, ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…They found that the satisfaction scores in the four phases of labor were significantly higher in the group that was administered a massage compared with the control group (Mortazavi et al, ). Similar results were shown in the study by Sethi and Barnabas (). In their study, it is stated that back massage had a significant impact on pain and that back massage had a significant role in the reduction of pain and the improvement of the emotional experience of labor (Sethi & Barnabas, ).…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were shown in the study by Sethi and Barnabas (). In their study, it is stated that back massage had a significant impact on pain and that back massage had a significant role in the reduction of pain and the improvement of the emotional experience of labor (Sethi & Barnabas, ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…[54] The pain rating index rank as measured by JPOM sensory and affective response in the present study supports the previous results. As massage seems to be effective in reducing shoulder pain intensity immediately after intervention; the present finding agrees with the study carried out by Sethi et al (2017), they concluded that the back massage had an impact on pain level. Therefore, it was demonstrated that back massage was effective to reduce the level of pain.…”
Section: Affective Description Of Shoulder Pain Responsesupporting
confidence: 92%